The impact of pectin supplementation on systemic inflammation pathways, gut microbiome, and metabolic health in patients with Metabolic Dysfunction-Associated Steatotic Liver Disease (MASLD): A study protocol for a randomised controlled trial - Noor Kifah Al-Tameemi; Jane I. Grove; Caroline L. Hoad; Jessica Wong Sun Wai; Adina Olaru; Saikat Mandal; Katie E. Rollins; Christopher R. Bradley; Susan T. Francis; Penny A. Gowland; Ana M. Valdes; Guruprasad P. Aithal (PLoS ONE, 2026)
Background Metabolic dysfunction–associated steatotic liver disease (MASLD) is the leading cause of chronic liver disease, affecting over 30% of adults worldwide. Emerging evidence suggests that dietary fibre, particularly pectin, may improve metabolic health by modulating inflammation, gut microbiota composition, and intestinal permeability. However, controlled human studies in MASLD are limited. This study aims to evaluate the effect of pectin supplementation on systemic inflammation, gut microbiome, and metabolic health in patients with MASLD. Methods This single-centre, double-blind, randomised, placebo-controlled dietary intervention will be conducted at Nottingham University Hospitals NHS Trust in partnership with the University of Nottingham. Thirty adults with MASLD will be randomised (1:1) to receive either 15g/day Low-methoxyl (LM) pectin or a matched placebo for six weeks. Each participant will attend baseline and post-intervention visits during which anthropometric data, fasting blood samples, and stool samples will be collected. FibroScan® assessments will be performed for all participants at both visits to quantify liver stiffness and steatosis. Twenty-two participants will take part in a magnetic resonance imaging (MRI) sub-study to evaluate hepatic and intestinal characteristics at baseline and post-intervention. Laboratory analyses will include liver function, lipid, glycemic, and inflammatory markers, alongside profiling of gut microbiota composition and short-chain fatty acids. Discussion This is the first randomised controlled study to evaluate the mechanistic effects of pectin supplementation on inflammation, gut microbiome composition, and metabolic outcomes in MASLD. The results may generate novel evidence on the role of soluble fibre in modulating the gut–liver axis and support the development of scalable, nutrition-based interventions to improve metabolic and hepatic health in this population. Clinical trial registration The trial was registered on ClinicalTrials.gov (Identifier: NCT07093346)